Sexual activity diminishes male virility in two Coccinella species: consequences for female fertility and progeny development - Michaud, J. P.; Bista, Mahadev; Mishra, Geetanjali; Singh, Omkar (My University, 2013)
Male contributions, both chemical and behavioural, can influence female sperm usage and reproductive success. To determine whether such male factors are subject to depletion in Coccinella septempunctata and Coccinella transversalis, we tested the effects of male mating history on male virility, as estimated by measures of mating behaviour, female reproductive success and progeny fitness, with parental age held constant. Overt measures of male mating effort (wriggling duration, number of shaking bouts and total copula duration) all diminished from virgin to 5 × mated males and were mirrored by concurrent declines in female fecundity and fertility (measured over 20 days). Paternal effects were also observed which diminished as a function of mating history, suggesting that transgenerational signals of male origin are also subject to depletion. Progeny of virgin fathers had higher rates of survival (C. transversalis) and faster development (both species) than progeny of 5 × mated fathers. Seminal fluid proteins are known to have allohormonal properties and can stimulate female fecundity and fertility in a number of insects, making them strong candidates for depletion as a function of mating activity. However, it is also possible that sperm limitation and/or reduced tactile stimulation of females by multiple-mated males may have contributed to some of the observed effects.
Citation: Michaud, J., . . . & Singh, O. (2013). Sexual activity diminishes male virility in two Coccinella species: consequences for female fertility and progeny development. Bulletin of Entomological Research, 103(5), 570-577. https://doi.org/10.1017/S0007485313000199
Keywords: Developmental time; Fecundity; Fertility; Paternal effects; Seminal fluid proteins